Social Class Oppression in Ally Condie's Crossed Novel: A Marxist Criticism - Eva Puspita; Singgih Kuncara; Fatimah M. (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
This study examined social class oppression in Ally Condie’s Crossed novel as the object of the research. This research applied Tyson’s social class and Young’s types of oppression theory. This research used qualitative research as a method and used a Marxist approach to conduct research. This research showed five indicators of social class: Aristocracy is portrayed as an Institution that has unlimited jobs and financial security. The upper class is the people in Tana provinces who are economically privileged which is they had small facilities for production. The middle class referred to the Officer, they worked with Institutions to oppress the lower class. The types of lower class refer to Ky, Vick, and Eli they were in dirty and disheveled clothes. Underclass refers to the Anomalies, they are alienated from society. This research also showed the third type of oppression; Exploitation was the Officers, and who get oppressed in this novel is the Aberration. In Marginalization, types of society that marginalize the Anomalies. In Powerlessness the oppressor is the Institution, and those who get oppressed are the Aberration, Anomaly, and the decoy. The existence of oppression was caused by social class and portrayed implicitly in society.